A non-uniform efficient grid type for GPU-parallel Shallow Water Equations models. (February 2017) - Vacondio, Renato; Dal Palù, Alessandro; Ferrari, Alessia; Mignosa, Paolo; Aureli, Francesca; Dazzi, Susanna
Abstract: A GPU-parallel numerical model for the solution of the 2D Shallow Water Equations, based on a novel type of grid called Block-Uniform Quadtree (BUQ), is presented. BUQ grids are based on a data structure which allows to exploit the computational capability of GPUs with minimum overheads, while discretizing the domain with non-uniform resolution. Different cases have been simulated in order to assess the efficiency of the BUQ grids. Theoretical and laboratory tests demonstrate that speed-ups of up to one order of magnitude can be achieved in comparison with uniform Cartesian grids. In the simulation of a hypothetical flood event induced by a levee breach in a real 83 km long river reach, with maximum resolution of 5 m, a ratio of physical to computational time of about 12 was obtained, opening scenarios of quasi real-time 2D simulations in large domains, still retaining a high resolution where necessary. Highlights: Shallow Water Equations parallel numerical scheme suitable for GPU. Novel Block-Uniform Quadtree (BUQ) grid-type, exploiting the computational capability of GPUs with non-uniform resolution. Very large domain can be simulated (38 km river reach) with high resolution (2 m). Speed-up of one order of magnitude is achieved, in comparison with Uniform resolution Cartesian Grids. High ratio between physical and computational time which enables real-time simulations.